Causes of houseless in-migration in Kanpur city, India - Shamshad (National Geographical Journal of India, 2023)
The present study aims to analyse the settlement and migration status of the houseless population and the reasons for their in-migration to Kanpur city. The study is based on a primary source of data generated through a comprehensive field survey in the city carried out in 2012. The study reveals that more than seventy percent of houseless people have their places of origin in the rural areas of the country and it is because of that that more than ninety percent of houseless persons are recorded as migrants in the city. The economic reasons, by far, predominate among the pull factors of houseless in-migration operating in the city in comparison to social and biological pull factors, as more than ninety percent of houseless in-migrants in the city are pulled by the economic factors, followed by the social and biological pull factors. Moreover, the jobs, regular work, and high wages in aggregate pulled more than half of the houseless in-migrants in the city, while, nearly forty percent of houseless in-migrants in the city are attracted by the quick payment, civic facilities, pomp & glare of the city, decent nature of work, nearness to the city and cheap city.